Penetapan Tarif Ambulans Untuk Evakuasi Medis Berbasis Unit Cost (Penelitian di AGD Dinas Kesehatan DKI Jakarta) - Kelvin E Riupassa; Narizma Nova; Endah Lestari; Sri Juniarti Azis; Wahyu Sulistiadi (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: An ambulance is a vehicle designed to be able to handle emergency patients, provide first aid and carry out intensive care while on the way to a referral hospital. Ambulance operations require a large amount of funds obtained from APBD funds through tariffs that were passed through the DKI Jakarta Governor Regulation five years ago. For this reason, a new tariff is required to adjust to current conditions. Objectives: The purpose of this study is to calculate the unit cost of ambulance services in DKI Jakarta to be a consideration in the tariff setting policy in DKI Jakarta province. Research Metodes: This study uses a quantitative descriptive approach to obtain information about the unit cost of the Jakarta ambulance production unit. The method used is the calculation of real cost using the basis of the causes of costs. This research was conducted at the DKI Jakarta Emergency Ambulance using secondary data on investment costs, operational costs and maintenance costs in 2018. Results: The total cost of emergency ambulance in 2018 is known that the proportion of three cost components, namely operational costs, is 76%, followed by investment costs of 20% and maintenance costs of 3%. The calculation of the total cost of medical evacuation using the double distribution method is Rp. 98,915,016,805.00 divided by the number of medical evacuations in 2018 of 37,564 activities, the unit cost of medical evacuation for the AGD of DKI Jakarta Health Office is Rp. 2,633,215.00 without subsidies. APBD costs, while if the subsidy component is included in the calculation, the unit cost for one trip to the AGD of the Health Office is Rp. 604,071.00. This is still far above the current tariff of Rp. 450.00, so the cost recovery rate (CRR) is still below. 100%. Conclusion: From the three cost components consisting of investment, operational and maintenance costs,the largest proportion was operational costs at 76%. The Cost Recovery Rate has not reached 100% so that the existing rates have not covered the costs incurred.